(3GdbGfhf aj GdWH GdbSe GdKGfjs - (3GdHdNj, CHh Ydj, GHf SjfG, GdQFjS, TQa Gdedc, GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG, (B428 (3g`s
(3ChdgG (B:s
(3bGd QMeg Gddg Gdaf GdKGfj jTJed Ydi LedJjf GdLedI GdChdi aj CMcGe GdCOhjI hGdCZPjI GdeaQOIs
(3BNQgG (B:s
(3fGbU GdBNQ, hBNQg(B: (3hdg eQGQI TOjOI hdg bHV hYahfI jfaY aj GHJOGA OGA GdKYdH hGdMSHI hYUGQJg JfaY aj GdLQH hGdMcI hNUhUG EPGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 241s
(3eYLe GdeDdajf(B: 1 / 618s
(3cTa GdXfhf(B: 2 / 1311s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdWHs